2010
DOI: 10.1007/s10584-010-9963-x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the effects of climate change on reproductive fitness of an endangered montane lizard, Eulamprus leuraensis (Scincidae)

Abstract: A shift in climatic conditions may directly modify critical organismal traits (such as reproductive output and offspring phenotypes), and experimental studies to document such direct effects thus may clarify the impacts of climate change on the species involved. The endangered Blue Mountains Water Skink (Eulamprus leuraensis) exhibits several traits predicted to imperil it under climate change: ectothermy, low reproductive output, specialisation to a restricted habitat type, montane endemicity, and a small geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 58 publications
2
22
0
Order By: Relevance
“…Not only does it appear that climate warming will benefit dams but also there are potential fitness benefits for the hatchlings of temperate ectotherms as a result of thermal effects during incubation. We found that hatchling mass was positively correlated with incubation temperature, as noted previously (Dubey and Shine, 2011), but not significantly affected by ovarian temperature (Fig.3). By what mechanism does incubation temperature influence hatchling traits?…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Not only does it appear that climate warming will benefit dams but also there are potential fitness benefits for the hatchlings of temperate ectotherms as a result of thermal effects during incubation. We found that hatchling mass was positively correlated with incubation temperature, as noted previously (Dubey and Shine, 2011), but not significantly affected by ovarian temperature (Fig.3). By what mechanism does incubation temperature influence hatchling traits?…”
Section: Discussionsupporting
confidence: 87%
“…However, there is not complete maternal control over embryonic developmental conditions ['maternal manipulation hypothesis' (Shine, 1995)], calling into question the effects of temperature variability on the ovarian cycle. While we know of no reports of temperature during the ovarian cycle of oviparous reptiles affecting subsequent hatchling traits (see also Dubey and Shine, 2011), the existence of latent thermal effects during incubation means that we must consider as a possibility both direct and latent effects of asymmetric warming during the ovarian cycle as well as during incubation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that changes in environmental temperatures experienced by gravid females or their eggs can influence embryonic development and the phenotypes of their offspring (e.g. Shine & Harlow 1993;Shine & Downes 1999;Du et al 2005;Dubey & Shine 2011). However, most of these studies involving oviparous species have evaluated the life history effects of constant temperatures rather than the fluctuating temperatures that constitute the natural thermal environment experienced by organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Ectothermic vertebrates depend on abiotic conditions to thermoregulate, and thus are extremely vulnerable to climatic fluctuations [14,15]. For example, temperature-dependent sex determination is widespread in reptiles such as lizards, turtles, and crocodiles, making these taxa particularly sensitive to abrupt variations in ambient temperature [16].…”
Section: Introductionmentioning
confidence: 99%